Pengaruh Pengadukan pada Degradasi Asam Humat Menggunakan Reaktor Mobile Heksagonal - Fauzan Yan Hawari; Rahadian Zainul; Syamsi Aini; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2022)
Humic acid is a heterogeneous organic compound that is toxic, mutagenic and carcinogenic. This study goals to degrade humic acid using the photocatalytic method. The photocatalyst used for degradation is nano ZnO doped Cu 7%. The degradation process applies sunlight using a hexagonal mobile reactor and the light intensity is measured using a lightmeter. The degradation was carried out with variation of stirring at 500 rpm and without stirring at 1, 2, 3, 4 and 5 hours of irradiation. Result of degradation analysed using UV-Vis spectrophotometer. Result obtained the degradation using stirring has a higher percentage of degradation than without stirring. The percentage maximum of degradation obtained in study was 90,09% with 500 rpm stirring at 5 hours irradiation. In this study showed the effect of stirring on humic acid degradation using a hexagonal mobile reactor.